2021
DOI: 10.18326/infsl3.v15i1.25-50
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of al-Ma’un Theology: The Movement of Muhammadiyah Educated Groups in Poverty Alleviation in Bulutellue Village, Sinjai Regency

Abstract: In the concept of Islamic community development, welfare is an ideal condition for any social life. Efforts to create prosperity in Bulutellue Village also received attention from the Muhammadiyah education group. They invite the community, especially those from the rich to provide sustainable assistance to groups of the poor and orphans as a form of mainstreaming al-Ma’un theology. This study aims to describe the implementation of al-Ma’un theology in alleviating poverty in Bulutellue Village, Sinjai Regency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Islah Gusmian observes that Muhammadiyah is one of the Islamic social organizations that contribute to the writing interpretations of the Qur'an in Indonesia [29]. According to Siti Mariatul Kiptiyah, the tradition of writing an interpretation of the Qur'an by Muhammadiyah members can be divided into two genres, Carakan script and Latin script [30] 7 . A sign of the history of Muhammadiyah's commentary that has existed for a long time is the Carakan Javanese interpretation of the Qur'an, which is Qur'an Jawen Muhamma-diyah and the Tafsir Kur'an Jawen Pandam lan Pandoming Dumadi which were published in 1927 and 1928, respectively.…”
Section: Offer Of the Study Of Interpretation Ofmuhammadiyah At Muham...mentioning
confidence: 99%
See 1 more Smart Citation
“…Islah Gusmian observes that Muhammadiyah is one of the Islamic social organizations that contribute to the writing interpretations of the Qur'an in Indonesia [29]. According to Siti Mariatul Kiptiyah, the tradition of writing an interpretation of the Qur'an by Muhammadiyah members can be divided into two genres, Carakan script and Latin script [30] 7 . A sign of the history of Muhammadiyah's commentary that has existed for a long time is the Carakan Javanese interpretation of the Qur'an, which is Qur'an Jawen Muhamma-diyah and the Tafsir Kur'an Jawen Pandam lan Pandoming Dumadi which were published in 1927 and 1928, respectively.…”
Section: Offer Of the Study Of Interpretation Ofmuhammadiyah At Muham...mentioning
confidence: 99%
“…Since its inception, Muhammadiyah has been a reflection of the interpretation of the verses of the Qur'an [4] by its founder K.H Ahmad Dahlan [5] 1 . The spirit of the Muhammadiyah movement also stems from the implementation of the interpretation of the verses into the realm of social practice [6]; [7] 2 . In addition, Muhammadiyah displays a characteristic as an organization with purification and modernist pattern [8].…”
Section: Introductionmentioning
confidence: 99%
“…Community interactions have the potential to form new knowledge that is believed to be the truth, for example, the industrial revolution 4.0 theories which many emphasize that the presence of this era will make it easier for humans to interact and work. In Muhammadiyah, they suggested to the rich group to give little fortune to the poor as the minstream of al-Ma'un techings (Rahman, Syukur and Jumadi, 2021). However, Salafi as a puritan Islamic movement by calling for purity and rejecting the forms of heretical teachings (Wiktorowicz, 2000), it has confirmed the position of Salafi on conservatism, separate from state intervention, and exclusive as an Islamic group (Yakin, 2018).…”
Section: Literature Review Salafi Women's Social Constructionmentioning
confidence: 99%
“…This is because the figure is considered to have an understanding and good practice in carrying out tèngka. Rahman et al (2021) concluded that social education became a very effective movement for change. In his research, he mentioned that the social education movement is social capital in forming patterns of social relations for the common welfare (Rahman et al, 2021) for internal and other community groups.…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al (2021) concluded that social education became a very effective movement for change. In his research, he mentioned that the social education movement is social capital in forming patterns of social relations for the common welfare (Rahman et al, 2021) for internal and other community groups. Other research states that local wisdom can be a reference in shaping human character with character, forming unity bonds, and uniting diversity in strong tolerance (Pranata et al, 2021)especially North Lombok in relation to the environment, nature, and plural social relations.…”
Section: Introductionmentioning
confidence: 99%